Inhaled liposomal ciprofloxacin in patients with non-cystic fibrosis bronchiectasis and chronic lung infection with Pseudomonas aeruginosa (ORBIT-3 and ORBIT-4): two phase 3, randomised controlled trials. Issue 3 (March 2019) - Haworth, Charles S; Bilton, Diana; Chalmers, James D; Davis, Angela M; Froehlich, Juergen; Gonda, Igor; Thompson, Bruce; Wanner, Adam; O'Donnell, Anne E
Summary: Background: In patients with non-cystic fibrosis bronchiectasis, lung infection with Pseudomonas aeruginosa is associated with frequent pulmonary exacerbations and admission to hospital for treatment, reduced quality of life, and increased mortality. Although inhaled antibiotics are conditionally recommended for long-term management of non-cystic fibrosis bronchiectasis with frequent exacerbations, there is no approved therapy. We investigated the safety and efficacy of inhaled liposomal ciprofloxacin (ARD-3150) in two phase 3 trials. Methods: ORBIT-3 and ORBIT-4 were international, randomised, double-blind, placebo-controlled, phase 3 trials run concurrently in similar geographical regions. Eligible patients had non-cystic fibrosis bronchiectasis, had had at least two pulmonary exacerbations treated with antibiotics in the previous 12 months, and had a history of chronic P aeruginosa lung infection. Patients were randomly assigned (2:1) to receive either ARD-3150 or placebo. ARD-3150 (3 mL liposome encapsulated ciprofloxacin 135 mg and 3 mL free ciprofloxacin 54 mg) or 6 mL placebo (3 mL dilute empty liposomes mixed with 3 mL of saline) was self-administered once daily for six 56-day treatment cycles, for 48 weeks. The primary endpoint was time to first pulmonary exacerbation from the date of randomisation to week 48. We did primary and secondary efficacy, safety, and microbiology analyses on the full analysis population, which comprised all randomised patients who received at least one dose of study drug. ORBIT-3 and ORBIT-4 are registered with ClinicalTrials.gov, numbers NCT01515007 and NCT02104245, respectively. Findings: Between March 31, 2014, and Aug 19, 2015, we screened 514 patients in ORBIT-3 and 533 patients in ORBIT-4. The full analysis populations consisted of 278 patients in ORBIT-3 (183 patients received at least one dose of ARD-3150 and 95 received placebo) and 304 patients in ORBIT-4 (206 patients received at least one dose of ARD-3150 and 98 received placebo). In ORBIT-4, the median time to first pulmonary exacerbation was 230 days in the ARD-3150 group compared with 158 days in the placebo group, a statistically significant difference of 72 days (hazard ratio [HR] 0·72 [95% CI 0·53–0·97], p=0·032). In ORBIT-3, the median time to first pulmonary exacerbation was 214 days in the ARD-3150 group and 136 days in the placebo group, a non-statistically significant difference of 78 days (HR 0·99 [95% CI 0·71–1·38], p=0·97). In a pooled analysis of data from both ORBIT-3 and ORBIT-4, the median time to first pulmonary exacerbation was 222 days in the ARD-3150 group and 157 days in the placebo group, a non-statistically significant difference of 65 days (0·82 [0·65–1·02], p=0·074). The numbers of adverse events and serious adverse events were similar in both groups in ORBIT-3 and ORBIT-4. Interpretation: In patients with non-cystic fibrosis bronchiectasis and chronic P aeruginosa lung infection requiring antibiotic therapy in the preceding year, ARD-3150 led to a significantly longer median time to first pulmonary exacerbation compared with placebo in ORBIT-4, but not in ORBIT-3 or the pooled analysis. Inconsistency between the trials suggests further research is needed into the heterogeneity of non-cystic fibrosis bronchiectasis and optimal outcome measures for inhaled antibiotics. Funding: Aradigm Corporation.